Can a Patient use an App at Home to Measure Knee Range of Motion? Utilizing a Mobile App, Curovate, to Improve Access and Adherence to Knee Range of Motion Measurements - Nirtal Shah; Corey Grunberg; Zahra Hussain (International Journal of Sports Physical Therapy)
# Introduction